My plain Jane - Hand, Cynthia, 1978-; Ashton, Brodi; Meadows, Jodi (Hand, Cynthia, 1978- Lady Janies, 2018)
You may think you know the story. Penniless orphan Jane Eyre begins a new life as a governess at Thornfield Hall, where she meets one dark, brooding Mr. Rochester--and, Reader, she marries him. Or does she? Prepare for an adventure of Gothic proportions, in which all is not as it seems, a certain gentleman is hiding more than skeletons in his closets, and orphan Jane Eyre, aspiring author Charlotte Bronte, and supernatural investigator Alexander Blackwood are about to be drawn together on the most epic ghost hunt this side of Wuthering Heights.